Violence : occupational hazards in hospitals - USA. National Institute for Occupational Safety and Health (Cincinnati, 2002)
Today more than 5 million U.S. hospital workers from many occupations perform a wide variety of duties. They are exposed to many safety and health hazards, including violence. Recent data indicate that hospital workers are at high risk for experiencing violence in the workplace. According to estimates of the Bureau of Labor Statistics (BLS), 2,637 nonfatal assaults on hospital workers occurred in 1999-a rate of 8.3 assaults per 10,000 workers. This rate is much higher than the rate of nonfatal assaults for all private-sector industries, which is 2 per 10,000 workers. Several studies indicate that violence often takes place during times of high activity and interaction with patients, such as at meal times and during visiting hours and patient transportation. Assaults may occur when service is denied, when a patient is involuntarily admitted, or when a health care worker attempts to set limits on eating, drinking, or tobacco or alcohol use. The purpose of this brochure is to increase worker and employer awareness of the risk factors for violence in hospitals and to provide strategies for reducing exposure to these factors.